Children as victims and as perpetrators – from symbolic incongruence to ineffective practice - Martins, Paula Cristina (2014)
Social representations about children and their problems are cognitive instruments that can be used as interpretative resources of children’s social place, the role and expectations assigned to them, their prescribed paths, and how social policies and legal systems carry out the symbolic and material regulation of their lives. As victimisation and offending are core topics within the field of Psychology of Justice, social representations of victims and offenders constitute relevant issues to be discussed. This is the case of child victims and child offenders. Starting from the assumption that child protection domain gives us a privileged perspective over childhood in contemporary societies, this paper addresses distinctive features of current symbolic configurations of children victimised and children offenders, considering their consistencies, contradictions and implications.